AIP Conference Proceedings 2009
DOI: 10.1063/1.3080921
|View full text |Cite
|
Sign up to set email alerts
|

Scaled simulations of a 10 GeV accelerator

Abstract: Abstract. Laser plasma accelerators are able to produce high quality electron beams from 1 MeV to 1 GeV. The next generation of plasma accelerator experiments will likely use a multi-stage approach where a high quality electron bunch is first produced and then injected into an accelerating structure. In this paper we present scaled particle-in-cell simulations of a 10 GeV stage in the quasi-linear regime. We show that physical parameters can be scaled to be able to perform these simulations at reasonable compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(48 citation statements)
references
References 11 publications
2
46
0
Order By: Relevance
“…This corresponds to a plasma wavelength of 106 m; then the onedimensional linear dephasing length, over which a plane wave pulse would slip in phase by relative to a speed-oflight particle bunch, is 1.84 m. Since performing such meter-scale simulations with explicit, laboratory-frame FDTD is intractable, even in 2D, we scale the simulation to higher density [40,41] to reduce the simulation size. While performing the simulation in a Lorentz boosted frame is another possibility for reducing the computational cost, we perform the test in the laboratory frame for several reasons.…”
Section: Implications For Simulations Of Lpa Stagesmentioning
confidence: 99%
“…This corresponds to a plasma wavelength of 106 m; then the onedimensional linear dephasing length, over which a plane wave pulse would slip in phase by relative to a speed-oflight particle bunch, is 1.84 m. Since performing such meter-scale simulations with explicit, laboratory-frame FDTD is intractable, even in 2D, we scale the simulation to higher density [40,41] to reduce the simulation size. While performing the simulation in a Lorentz boosted frame is another possibility for reducing the computational cost, we perform the test in the laboratory frame for several reasons.…”
Section: Implications For Simulations Of Lpa Stagesmentioning
confidence: 99%
“…We verify that the data agrees for different values of γ boost , which is the relativistic factor of the frame of the simulation, including for γ boost = 1 (laboratory frame) for 100 MeV and 1 GeV LPA stages. We use boosted frame simulations to study the evolution of an externally injected beam in a meter scale LPA stage with parameters similar to what was presented in [13]. The simulations are done in two-dimension, which is suitable for LPA stages in the quasi-linear regime.…”
Section: Simulations Of 10 Gev Stages In the Boosted Framementioning
confidence: 99%
“…Here we show that high order laser modes can be used in quasilinear stages to control the focusing forces, and therefore the transverse beam dynamics, and the importance of such control for improving beam loading of the accelerator and efficiency We describe design studies which have characterized regimes of operation for quasilinear stages with Gaussian lasers, and show that these results indicate the desirability of controlling the focusing forces on the bunch for beam loading of low emittance beams Simulations in conjunction with theory are then used to demonstrate control over focusing by selecting the ratios of the modes, their delay and other parameters, and to show how this control can enable efficient stages for low emittance beams, including compensation for the effects of the plasma channel required to guide the laser driver and for mild nonlmearity (for further detail see [17,18]) QUASILINEAR STAGE DESIGN AND REGIME Scalable stage designs in the quasilinear regime have been developed which predict performance at any density and hence stage energy (so long as the plasma period remains much longer than the laser wavelength) using a single simulation. This allows prediction of performance over a wide parameter range including GeV light source stages and 1-10 GeV collider relevant stages among others.…”
Section: Introductionmentioning
confidence: 99%
“…Laser-plasma wakefield accelerators [ 1 ] achieve accelerating electric fields thousands of times those of conventional accelerators by using the radiation pressure of an intense laser to drive a plasma wave (review [2]) Such accelerators have recently demonstrated quasi-monoenergetic electron beams [3][4][5] at up to GeV energies [6,7] and with good stability [6,7], and are being developed to support applications such as future high energy physics colliders [8], and efficient high quality accelerators near 0 5 GeV for Thomson gamma sources in nuclear security [9] and as drivers for free electron lasers [10] For such applications, a key requirement is accelerator stages that accomplish efficient transfer of the laser energy into low-emittance electron (and, in the case of colliders, positron) beams Recent work has demonstrated design of stages that efficiently transfer laser energy into a particle bunch in the nonlinear [11,12] and quasi-linear [13,14] regimes In the highly nonlinear 'blow-out' regime the plasma electrons are completely evacuated, and the remaining ion column provides a fixed, linear focusing for electrons [15] Positron focusing is present only over a small phase range and is not linear On the other hand, driving the wake at lower amplitude produces symmetric acceleration and focusing for electrons and positrons By driving the wake at the largest amplitude where it remains nearly sinusoidal, typically near ao ~ 1, with ao the dimensionless laser amplitude [16], accelerating gradients can be large while retaining nearly symmetric positron behavior [13] In addition, in the linear and quasilinear regimes the transverse mode shape of the laser can be used to control the focusing forces on the particle bunch, which can be important for ermttance matching of the bunch to the structure [17,18])…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation